Status and Prospects for Increasing Production and Export Indonesian Ginger - EKWASITA RINI PRIBADI (Perspektif, 2013)
Indonesian ginger production rate decreased 13.3% per year in the last decade, and put Indonesia into a position to the 14 ginger exporter countries which was originally the main exporting country, due to the decline rate of productivity during the period 2004-2011. Over the periode of 2004 to 2011, the decline productivity reached of 5,88% per year and harvested area 2,03% per year. The decline productivity as the impact of the use of carelessly seed, pest and disease, application of unappropriate cultivation techniques, climate change, and competition with more profitable commodities, so that influences to the rate of planted area. To be able to compete in the free market, the strengthening of farmer capital and infrastructure improvements policy along with assistance for the implementation of cultivation techniques in accordance to the GAP (Good Agricultural Practices) and GMP (Good Manufacturing Practices), and the use of of superior varieties, healthy seeds, and socialization good agriculture practices needs to be done. In the future, research to generate high yielding varieties resistant to pest and bacterial wilt disease and high moisture, as well as cultivation technology that can overcome climate change should be carried out. Key words : ginger, production, export, determinats factor